2016
DOI: 10.1037/vio0000026
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between research and practice by strengthening academic-community partnerships for violence research.

Abstract: Objectives:This commentary seeks to highlight the benefits of community-based participatory research (CBPR) and promote its use in the violence field. Community perspectives remain underrepresented in the CBPR literature despite the emphasis on equitable partnerships and shared ownership in the research process. Method: Informal interviews were conducted with 10 community partners to understand their perspectives on using and participating in research. Results: Several recommendations for strengthening academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 28 publications
0
41
0
Order By: Relevance
“…There is a vast continuum of community engagement in research, from involving community members in all aspects of a project including conception, development, and data collection, to community playing merely an advisory role, to using broader public venues for dissemination of research results (Lesen 2015;Yuan et al 2016). The extent and methods of community engagement or public participation should ideally be designed to respond to the goals for a project (Cumberbatch 2015).…”
Section: Our University-community Partnershipsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a vast continuum of community engagement in research, from involving community members in all aspects of a project including conception, development, and data collection, to community playing merely an advisory role, to using broader public venues for dissemination of research results (Lesen 2015;Yuan et al 2016). The extent and methods of community engagement or public participation should ideally be designed to respond to the goals for a project (Cumberbatch 2015).…”
Section: Our University-community Partnershipsmentioning
confidence: 99%
“…The intertwined social and environmental challenges facing communities across the globe create a pressing need for place-based, use-inspired, policy-relevant research about disasters and environmental change (Wall et al 2017). In striving to meet this need, scholars must critically scrutinize their research practices to incorporate collaborative problem-solving, co-production of knowledge, democratic public participation, and ethical, equitable researcher-community partnerships into their methodologies (Chilvers and Kearnes 2015; Yuan et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBPR's benefits are well documented across disciplines (e.g., Collins et al, 2018;Green, 2007;Lightfoot et al, 2014;Lindamer et al, 2008;O'Brien et al, 2018;Yuan et al, 2016). These benefits include researchers' ability to utilize research outcomes to advocate for clients (Gray & Price, 2014;Horowitz et al, 2009;McElfish et al, 2015), advance health disciplines (O'Fallon & Dearry, 2002;Israel et al, 2013), increase participant contributions (Case et al, 2014;Wagstaff, Graham, Farrell, Larkin, & Tatham, 2018), address multifaceted client issues (Corrigan, Pickett, Kraus, Burks, & Schmidt, 2015), improve mental health services (Case et al, 2014), and foster interprofessional relationships (Hergenrather, Geishecker, Clark, & Rhodes, 2013).…”
Section: Community-based Participatory Researchmentioning
confidence: 99%
“…Research has shown that program evaluation provides opportunities for reflection on past and future programming, helps programmers to better understand and improve service delivery, and showcases effectiveness of a program to key stakeholders and the community (Fitzpatrick, Sanders, & Worthen, 2004). Further, when community organizations partner with research partners, there is the benefit of not only bridging the gap between research and practice (Ferguson, 2005;Yuan et al, 2016), but also allowing for a collaborative learning environment that capitalizes on both partners' expertise (MacPherson & Hall, 2011).…”
Section: Next Steps Future Recommendations and Conclusionmentioning
confidence: 99%